(untitled) (Revista Contexto & Educação, 2026)
Science communication is fundamental to bringing scientific knowledge closer to society, especially in a context of rapid information dissemination. Social networks, such as TikTok, have stood out as strategic spaces for this communication, mainly among young audiences. This study investigates the profiles with science communication videos that had the highest engagement between April 24 and May 6, 2025, through an exploratory analysis of content published with the hashtag #divulgaçaocientifica (scientific communication). The results indicate that the most popular profiles use strategies such as colloquial language, humor, dynamic audiovisual resources, and charismatic performance. However, profiles that disseminate false information were also identified, signaling challenges in science communication on social networks. The study highlights the importance of effective communication strategies to increase the visibility of science and strengthen scientific culture through digital platforms.